Preparation And Characterisation Of Ethylene Vinyl Acetate/Natural Rubber/Mengkuang Leaf Fibre Thermoplastic Elastomer Composites - Faiezah, Hashim (2019)
Thermoplastic elastomers composites are a ternary blend, which consist of thermoplastics and elastomers as matrix phase and natural fibre as dispersed phase. The end performance of the composites is explained on the basis of combined behaviour of the natural fibre, polymer matrix and fiber/matrix interface. Thus, in this study, thermoplastic elastomer composites based on ethylene vinyl acetate (EVA), natural rubber (NR) and mengkuang leaf fibre (MLF) were developed. Firstly, the best blending sequences was studied to produce composites with the best end properties. The EVA:NR ratio was fixed at 50:50 while the MLF loadings were varied from 0 to 10 phr. It was found that better enhancement in the end properties were achieved when EVA was blended with NR first before the addition of MLF. This system produces the composites with the best fiber dispersion in the matrix, resulting in low stabilization torque, good tensile properties, and better thermal stability, compared with the other systems. Secondly, fiber modification through alkaline peroxide bleaching treatments were examined. The treatment was found to be effective in removing surface impurities, lignin and hemicellulose, thereby producing a rougher fibre surfaces which promote a good fibre/matrix adhesion, as depicted by Scanning Electron Microscopy (SEM), thus resulting better tensile properties and thermal properties. Furthermore, the treatment were resulted in the reduction of water absorption from 31% to 26%. Next, comparison between EVA/NR/MLF and EVA/(epoxidized natural rubber) ENRxxvi 50/MLF composites were evaluated. It was found that, the EVA/ENR-50/MLF composites showed lower stabilization toque, higher tensile and thermal properties than EVA/NR/MLF composites. These results indicated that the EVA/ENR-50/MLF composites had better compatibility than the EVA/NR/MLF composites. This result was probably due the interaction between the carbonyl group of the EVA and the epoxy group of the ENR-50 and the formation of hydrogen bonds between the MLF and the EVA/ENR-50 matrix. However, the presence of ENR-50 had further increased the water absorption of the blend and composites due to oxirane group present in the ENR-50. Lastly, the influenced of different types of vulanisation system namely sulfur and peroxide curing systems were evaluated. The stabilization torque of vulcanized composites exhibited higher value compared to its unvulcanized counterparts as the effect of the crosslinking. Dicumyl peroxide (DCP) cure system showed higher improvement in tensile strength and modulus compared to sulfur vulcanizates. However, sulfur cure system showed better resistance towards thermal degradation compared to peroxide system. This was attributed to the DCP that was caused degradation in polymer chain or chain scission in the composites at high temperature.